GAMBARAN SIKAP KEWIRAUSAHAAN DAN NIAT BERWIRAUSAHA PADA MAHASISWI ANGKATAN 2014 DI UPI BANDUNG - Rahayu, Widiana; Mulyadi, Hari; Utama, Dian Herdiana (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Purpose - The purpose of this study is to see the description of entrepreneurial attitude and entrepreneurship intention.Design/Methodology/Approach - The design of this study is cross sectional by using descriptive approach with explanatory survey method and total of 145 respondents. A questionnaire was used as a research instrument to collect data from respondents. Analytical technique used is descriptive technique by using frequency distribution.Findings - Based on the results of the research using descriptive analysis, the results obtained that the entrepreneurial attitude is in the medium category with a score of representative 63,5% and entrepreneurship intention is in the medium category with a score of representative 65,3%.Originality/Values - The difference of this study with previous research is on the object studied at female students 2014 in UPI Bandung who have pass studied Entrepreneurship studied, the measurement of entrepreneurship attitude through the dimension of Theory Planning Behavior (TPB) Icek Azjen in 1991 about autonomy authority, opportunity economy, self-realization, and perceived self-confidence.